074 Implementation of Grade Methodology in Recommendation Development. (15th August 2013) - Haynes, J; Regidor, D; Chan, W
Abstract : Background: We have been developing CPGs for use within our organisation since 2002. Our lengthy, text- based rationales were not widely read by guideline users. We created a decision support (rationale) table, based on GRADE methodology, and added a summary statement (basis of recommendation) to allow readers a concise and transparent snapshot of our justification for recommendation and strength. Context: The rationale serves as a bridge between systematic review and recommendation, and provides users with a high-level justification for a recommendation. The basis of recommendation (BoR) summarises the 4 GRADE domains of strength of recommendation and how they are integrated to derive the final recommendation and strength. The BoR serves to: Provide information to the Guideline Development Team and frontline clinicians to facilitate discussion, consensus and aid clinical decision-making. Provide a structured, standardised portal into more detailed information in the CPG. Description of Best Practice: We follow GRADE's 2-level designation of recommendation strength (strong/weak), and developed standardised recommendation language to align with recommendation strength. We considered two approaches to derive the final recommendation strength, finally settling on an approach that allows flexible weighting of the contribution of each domain to recommendation strength. With this approach, in special circumstances, a strong recommendation may be given in the absence of a high-level of certainty. We plan to provide direct links from the CPG to our electronic medical record's decision support tools. Lessons for Guideline Developers, Adaptors, Implementers, and/or Users: A concise and targeted rationale helps clinicians understand how evidence is used to develop clinical practice recommendations.